Densified biocoal from woodchips: Is it better to do torrefaction before or after densification? - Ghiasi, Bahman; Kumar, Linoj; Furubayashi, Takaaki; Lim, C. Jim; Bi, Xiaotao; Kim, Chang Soo; Sokhansanj, Shahab (Pergamon Press Ltd., 2014)
Torrefied biomass represents a high quality renewable energy commodity that can be used to substitute fossil fuels such as coal. However, densification processes such as pelletisation is necessary to improve the tradability of "low-dense" torrefied biomass. In this work, two process pathways were assessed for energy and mass balance in making torrefied pellets from softwood chips and qualities of the resulting torrefied pellets were compared. Pathway I involve drying the wood chips, torrefaction, grinding followed by densification. In pathway II, wood chips were dried, ground, densified and finally torrefied. The results showed that it was difficult to bind the torrefied biomass particles and a binding agent was necessary to enable their effective pelletisation with reasonable energy consumption. In contrary, pelletization of raw materials was possible without using binding agents and when the "raw wood pellets" were torrefied, the pellets surprisingly stayed intact and had several promising properties such as higher energy/carbon value, reduced moisture content and higher stability in water. In addition, the pathway II was more efficient in terms of overall energy and material balance. (C) 2014 Elsevier Ltd. All rights reserved.